Cholestasis as Primary Manifestation of Cytomegalovirus Infection: A Case Report - Handayani, Dyah Suci; Kadim, Muzal (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Jaundice, marked by yellow discoloration of the sclera, skin, and mucous membranes due to bilirubin accumulation, can be physiological in neonates but may also signal pathological conditions like cholestasis. Cholestasis is commonly associated with biliary atresia; however, it can arise from various causes such as cytomegalovirus (CMV) infection. Thus, this study aims to discuss the diagnostic approach on neonatal cholestasis as the main manifestation in CMV infection. Case: A 2-years-old boy referred to the hospital with chief complaint of jaundice in both eyes and skin since 4 days of age and persisted until the age of 40 days old. Abdominal ultrasound in prior hospital revealed obstruction of bile duct which indicative for biliary atresia. However, subsequent abdominal and ARFI ultrasound showed no showed results inconsistent with biliary atresia. Furthermore, other examinations indicating infection, which were confirmed as CMV infection through serological and PCR test. Patient was then treated using valganciclovir treatment. Discussion: The diagnostic approach for cholestasis includes comprehensive anamnesis and physical examination, laboratory tests including complete blood count, bilirubin levels, liver function analysis, and coagulation factors, as well as ultrasound. CMV infection should be considered a potential cause of neonatal cholestasis, even in the absence of specific manifestations beyond jaundice and gastrointestinal symptoms. Conclusion: CMV infection can present solely with cholestasis and gastrointestinal symptoms, without other typical CMV manifestations. Thus, comprehensive evaluation, CMV screening, and careful assessment of the patient’s condition are essential for accurate management.